Evaluating the effect of the pin's length to the strength of double sides friction stir welded aluminum - Darmadi, Djarot Bangun; Mentary, Annisha; Yusup, E.M.; Mahzan, S. (International Journal of Integrated Engineering, 2019)
Based on previous research, it is believed that the double side friction stir welding will improve the obtained joint. It is hoped the length of the pin broaden the strain hardened area (especially the interference zone) which in turn will produce the stronger joints. From tensile test data, the tensile strength does increase by the length of the pin. The maximum tensile strength of 183 MPa acquired from the 6.5 millimeter pin which is equal to 75% joint efficiency whilst the lowest is 42 MPa resulted by the 2.5 millimeter pin. The hardness test confirmed the existing of the strain hardening phenomenon, which was shown by harder materials at interference zone. Other supporting evidence is the micro structure photo. The photos showed that not only exhibits strain hardening the interference zone also yields finer dispersed micro structure that will provide stronger joint.